Findbuch der Bestände Abt. 51 bis Abt. 55: Abt. 51 Regierungen der Herzogtümer während der Erhebung 1848-1851 / Abt. 52 Dänische Immediatkommission zur gemeinsamen Regierung der Herzogtümer in Sonderburg 1848-1849 / Abt. 53 Landesverwaltung für das Herzogtum Schleswig 1849-1851 und Dänischer Regierungskommissar 1850-1851 /Abt. 54 Oberste Zivilbehörde für das Herzogtum Holstein in Kiel 1851-1852 - Rathjen, Jörg (Veröffentlichungen des Landesarchivs Schleswig-Holstein, 2010)
During the perioad of the revolutionary movement in Europe in March 1848, the German-Danish nationalities conflict led to the Schleswig-Holstein census (1848-1851). At the beginning, new civil and military administrative structures were created in the duchies to replace the old national authorities. This find book documents the tradition of the activities of the Schleswig-Holstein and Danish authorities established between 1848 and 1851/52 in the Schleswig-Holstein State Archives. It comprises a total of around 94 meters and provides insights into the administrative processes and events of those turbulent, eventful years. Personnel matters are an important focus of military tradition. In this context, it should be noted in particular that there is an almost complete inventory of documents of military justice (auditoria) on offences committed by individual soldiers.